2016
DOI: 10.1108/jfc-04-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

Internal controls and fraud – empirical evidence from oil and gas company

Abstract: Purpose The purpose of this study is to examine the type of internal control weaknesses and its impact that leads to fraud activities in an oil and gas company, which is rarely found in empirical research. Design/methodology/approach A case study approach was taken to investigate and analyse the fraud incidents to the deepest understanding. A mixed method of data collection, specifically document analysis and interviews, was used. Findings The study found that internal control weaknesses can be major contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
0
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 28 publications
10
84
0
18
Order By: Relevance
“…However, internal control do not influence to fraud prevention of procurement. This finding is consistent with prior research by [14]. The research result also find that internal audit has a positive impact to fraud prevention.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, internal control do not influence to fraud prevention of procurement. This finding is consistent with prior research by [14]. The research result also find that internal audit has a positive impact to fraud prevention.…”
Section: Discussionsupporting
confidence: 92%
“…Internal control can be described as policies and procedures established to provide reasonable assurance that the specific entity objectives will be achieved [14]. Internal control is expected to ensure integrity, accountability, and transparency in the procurement process.…”
Section: Internal Control and Internal Auditmentioning
confidence: 99%
See 1 more Smart Citation
“…Kesempatan yang muncul ti dak hanya dari tidak adanya budaya antike curangan di organisasi. Pengendalian inter nal yang lemah diketahui juga sebagai faktor yang membuat kecurangan terjadinya kecu rangan (Kabuye, Nkundabanyanga, Opi so, & Nakabuye, 2017;Rendon & Rendon, 2016;Zakaria, Nawawi, & Salin, 2016).…”
Section: Lemahnya Budaya Anti Kecurangunclassified
“…Regarding internal control of accounting fraud, prior studies concluded that internal control system plays a significant role to prevent the actions of fraudulent behavior (Suh, Nicolaides and Trafford, 2019;N'Guilla, Basiruddin, Mohammad & Rasid (2018Nawawi and Salin, 2018;Putri and Irwandi, 2016;Zakaria, Nawawi, & Salin, 2016;Siregar and Tenoyo, 2015;Ionescu,2010). A poorly designed Internal Control System can result in a weak corporate control that creates an opportunity for someone to conduct fraudulent behavior that can harm an agency or institution.…”
Section: Introductionmentioning
confidence: 99%